INOVASI PEMBELAJARAN IPS BERBASIS GOOGLE SITES DALAM MENGAKOMODASI GAYA BELAJAR YANG BERAGAM PADA MURID SMP KELAS VII - Binti Mar’atus Sholihah; Toto Nusantara (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The diversity of students’ learning characteristics calls for social studies learning media that does not rely on a single mode of presentation. The condition of Class VII-D at SMP Negeri 25 Malang revealed the use of textbooks, oral explanations, and relatively repetitive videos, limiting students’ opportunities to interact with learning materials in different ways. This study describes the design of Google Sites-based social studies learning media that accommodates the diverse learning characteristics of seventh-grade students, determines its validity based on assessments by media and subject-matter experts, and examines its feasibility based on assessments and user responses. The development employed Research and Development (R&D) using the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation, and involved 28 students from Class VII-D. Data were collected through observations, interviews, a needs-analysis questionnaire, expert validation sheets, and student response questionnaires, and were analyzed using descriptive quantitative and qualitative approaches. The product integrates text, images, infographics, videos, Padlet, Wordwall, and Zep Quiz. Media expert validation reached 99% (very valid and highly feasible), while subject-matter expert validation reached 80% (valid and feasible); student responses reached 86% (very good). These findings position the developed media as a feasible digital alternative for supporting social studies learning through more diverse learning experiences. ABSTRAK Keberagaman karakteristik belajar murid menuntut media pembelajaran IPS yang tidak berhenti pada satu cara penyajian. Kondisi kelas VII-D SMP Negeri 25 Malang memperlihatkan penggunaan buku paket, penjelasan lisan, dan video yang relatif berulang, sehingga pilihan murid dalam berinteraksi dengan materi masih terbatas. Penelitian ini mendeskripsikan desain media IPS berbasis Google Sites yang mengakomodasi keberagaman karakteristik belajar murid kelas VII, mengetahui tingkat kevalidannya berdasarkan penilaian ahli media dan ahli materi, serta mengetahui tingkat kelayakannya berdasarkan penilaian dan respons pengguna. Pengembangan dilakukan melalui Research and Development (R&D) dengan model ADDIE yang meliputi Analysis, Design, Development, Implementation, dan Evaluation, melibatkan 28 murid kelas VII-D. Informasi penelitian diperoleh melalui observasi, wawancara, angket analisis kebutuhan, lembar validasi ahli, dan angket respons murid, lalu dianalisis secara deskriptif kuantitatif dan kualitatif. Produk mengintegrasikan teks, gambar, infografis, video, Padlet, Wordwall, dan Zep Quiz. Validasi ahli media mencapai 99% (sangat valid dan sangat layak), sedangkan ahli materi memperoleh 80% (valid dan layak); respons murid mencapai 86% (sangat baik). Temuan tersebut menempatkan media yang dikembangkan sebagai alternatif digital yang layak untuk mendukung pembelajaran IPS dengan pengalaman belajar yang lebih beragam.